Eucalyptus Agroforestry in Tea Plantation on the Mambilla Plateau: Influence on Carbon Sequestration and Soil Organic Carbon - Aikpokpodion, Paul E. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Tea-Eucalyptus intercropping is common on the Mambilla plateau in order to maximize land use and increase financial income. Carbon sequestration potential of Eucalyptus and effect on soil organic carbon was evaluated. Non destructive method was used in calculating the amount of carbon sequestered in eucalyptus trees while wet chemistry was used in the determination of soil physicochemical properties. Result showed that an average of 19.48 kg CO2 was sequestered in each tree while soil macro and micronutrients were enhanced in soil cropped with tea-eucalyptus intercrop compared with adjacent tea plantation without eucalyptus trees. Intercropping tea with eucalyptus could be a means of atmospheric CO2 removal and consequently being a potential choice for carbon trading.